Use of supracutaneous bone plating for management of radius/ulna and tibia/fibula fractures in dogs - KUMAR, AMIT; KAUR, ASHMEET; SINGH, SUKHPREET; TYAGI, S P; KUMAR, ADARSH (The Indian Journal of Animal Sciences, 2023)
The study was done with the objective to utilize supracutaneous bone plating as a mean of minimally invasive osteosynthesis for management of radius/ulna and tibia/fibula fractures in dogs. Nine cases of long bone fracture (2 radius/ulna and 7 tibia/fibula fracture) in dogs having body weight 8-20 kg and age 4 months to 2 years were repaired with supracutaneous bone plating (minimally invasive plate osteosynthesis) under general anaesthesia after a thorough physical, orthopaedic, neurological and radiographic examinations. Intra-operatively, 3.5 mm, locking head-limited contact-dynamic compression plate (LH-LC-DCP) was used in locking mode with insertion of two self-tapping locking head cortical screws of 3.5 mm (of varying length) in each proximal as well as distal fracture. The bone plate was applied on the medial surface of radius and tibia. Postoperative radiographs were taken to assess the status of fracture reduction and fixation which was good in all the cases. Regular follow-ups showed good fracture reduction as well as fixation with no changes in implant position. Loosening of screws was observed in single case with no other complication in any of the cases. All the implants were removed on or before 68th day after surgery under sedation. All the animals showed good weight bearing with near to normal limb function on final day of the reappraisal. The supracutaneous bone constructs provided good reduction and fixation at fracture site similar as external skeletal fixators not compromising on axial and torsional stiffness.